Biologia reprodutiva e polinização de espécies simpátricas de Diplusodon (Lythraceae) - Granja E Barros, Mariliza A. (Instituto de Ecología, A.C., 1996)
The reproductive biology and pollination of Diplusodon crulsianus Pohl, D. oblongus Pohl, D. ramosissimus Pohl, D.  rosmarínifolius St. Hil, and D. villosus Pohl, were investigated  during 1985, 1986 and 1 991. These species occur sympatrically in "cerrados" (savanna-like vegetation) of the Federal District (Brazil), where they flower synchronously, D. oblongus with D.  villosus (January to April) and D. crulsianus with D. ramosissimus and D. rosmarínifolius (May to August). Differences in leaf  morphology, presence or absence of tomentum on the  vegetative and floral structures and stamen number, separate  the species. Diplusodon flowers have diurnal anthesis, flowers  are magenta-colored contrasting with the yellow stamens and show some degree of enantiostyly. Trigona spinipes L., Augochioropsis spp. and Apis mellifera L. were considered potential pollinators. Diplusodon species are xenogamous with  facultativo autogamy in D. crulsianus and D. villosus (16% and  17 %).